PENGARUH PROFITABILITAS, FREE CASH FLOW, LIKUIDITAS, DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN - Yunita, Erlinda Vira; Subardjo, Anang (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This research aimed to examine and analyzed the effect of profitability, free cash flow, liquidity, and investment opportunity set on the dividend policy. Profitability calculated by return on asset, free cash flow was calculated by net value from the fluctuation of cash flow from the activity of comnpany operation was divided by assets total on the same periods. Meanwhile, liquidity was measured by the current ratio, while the set of investment opportunities was calculated by indicator market value Assets to book value Assets.This research was a quantitative approach. The sample of this research used a purposive sampling method, i.e. the sample collection technique with determine criteria. Based on the beverage listed Indonesia Stock Exchange in 2015-2019, therefore it obtained 51 observation data. In addition, the analysis method used multiple linear regressions with the instruments SPSS porgram.The result of the research showed that free cash flow, liquidity, and investment opportunity set did not have any effect on the dividend policy, while profitability had a positive effect on the dividend policy.